AMPK involvement in endoplasmic reticulum stress and autophagy modulation after fatty liver graft preservation: a role for melatonin and trimetazidine cocktail. Issue 1 (29th March 2013) - Zaouali, Mohamed Amine; Boncompagni, Eleonora; Reiter, Russel J.; Bejaoui, Mohamed; Freitas, Isabel; Pantazi, Eirini; Folch‐Puy, Emma; Abdennebi, Hassen ben; Garcia‐Gil, Francisco A.; Roselló‐Catafau, Joan
Abstract: Ischemia/reperfusion injury (IRI) associated with liver transplantation plays an important role in the induction of graft injury. Prolonged cold storage remains a risk factor for liver graft outcome, especially when steatosis is present. Steatotic livers exhibit exacerbated endoplasmic reticulum (ER) stress that occurs in response to cold IRI. In addition, a defective liver autophagy correlates well with liver damage. Here, we evaluated the combined effect of melatonin and trimetazidine as additives to IGL‐1 solution in the modulation of ER stress and autophagy in steatotic liver grafts through activation of AMPK. Steatotic livers were preserved for 24 hr (4°C) in UW or IGL‐1 solutions with or without MEL + TMZ and subjected to 2‐hr reperfusion (37°C). We assessed hepatic injury (ALT and AST) and function (bile production). We evaluated ER stress (GRP78, PERK, and CHOP) and autophagy (beclin‐1, ATG7, LC3B, and P62). Steatotic livers preserved in IGL‐1 + MEL + TMZ showed lower injury and better function as compared to those preserved in IGL‐1 alone. IGL‐1 + MEL + TMZ induced a significant decrease in GRP78, pPERK, and CHOP activation after reperfusion. This was consistent with a major activation of autophagic parameters (beclin‐1, ATG7, and LC3B) and AMPK phosphorylation. The inhibition of AMPK induced an increase in ER stress and a significant reduction in autophagy. These data confirm the close relationship between AMPK activation and ER stress and autophagy after cold IRI. The addition of melatonin and TMZ to IGL‐1 solution improved steatotic liver graft preservation through AMPK activation, which reduces ER stress and increases autophagy.